Spectral behaviour of hybrid Raman-erbium random fiber laser with dual pumping - Mohd Yusoff, N.; Zainol Abidin, N. H.; Abu Bakar, M. H.; Abdul Hadi, M. A. W.; Mahdi, M. A. (Elsevier GmbH, 2020)
This paper experimentally demonstrates the spectral behaviour of a hybrid Raman-erbium random fiber laser that employs dual pumps; a 1497 nm pump on one end and a 1455 nm pump on the other end. The 80 km open-ended scheme is investigated through power variation of the pumps. A dual wavelength laser with minimal disparity between peaks is achieved. However, the addition of 1497 nm pump to the hybrid scheme is detrimental to the dual-wavelength performance in terms of achieving stable operating regime. It is believed that the findings and discussion from this work will contribute to the understanding of spectral dynamics based on the interplay between hybrid gain and dual pump source. The results from this investigation may also serve as a pertinent guidance in the design of dual- and multiwavelength random fiber lasers.